Impact of School Gardens on United Arab Emirates Science Students’ Learning Environment Perceptions, Attitudes, Aspirations and Knowledge - Baini, William (Curtin University, 2020)
This study examined whether using a school garden in secondary science classes improved student outcomes. The pre-post design involved administrating three surveys and a test to 268 students. The results indicated that, after using school gardens, students reported statistically significantly higher scores in terms of learning environment perceptions, aspirations towards gardening, and knowledge of healthy eating. The study provides evidence of the benefits of school gardens to different stakeholders: policy developers, school administrators and teachers.